THE EFFORTS OF SINGKAWANG BATIK COMMUNITY TO REALIZE EQUALITY AND WELFARE OF WOMEN AND DISABILITY GROUP - Ulmi, Tiara Fahmiyatul; Komariah, Siti; Wilodati, Wilodati (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
Equality and welfare need to be realized for women and groups with disabilities. To realize this, various efforts are needed. The purpose of this study is to explain the strategies and roles carried out by the Singkawang City Batik community in realizing equality and welfare for women and groups with disabilities through local wisdom. The method in this research is a qualitative case study. The results of the study show that equality and welfare for women and groups with disabilities are interconnected and influence each other, and to realize equality and welfare for women and groups requires special strategies. The conclusion from this study is that the efforts of the Batik Kote Singkawang community to realize equality and welfare for women & groups with disabilities through empowerment have been carried out through a strategy, namely empowering women and groups with disabilities based on local wisdom and carrying out roles according to what is needed by empowerment participants, namely mentors, motivators and facilitator.